A horizon scan exercise for aquatic invasive alien species in Iberian inland waters - Oficialdegui, F. (2023)
As the number of introduced species keeps increasing unabatedly, identifying and prioritising current and potential Invasive Alien Species (IAS) has become essential to manage them. Horizon Scanning (HS), defined as an exploration of potential threats, is considered a fundamental component of IAS management. By combining scientific knowledge on taxa with expert opinion, we identified the most relevant aquatic IAS in the Iberian Peninsula, i.e., those with the greatest geographic extent (or probability of introduction), severe ecological, economic and human health impacts, greatest difficulty and acceptability of management. We highlighted the 126 most relevant IAS already present in Iberian inland waters (i.e., Concern list) and 89 with a high probability of being introduced in the near future (i.e., Alert list), of which 24 and 10 IAS, respectively, were considered as a management priority after receiving the highest scores in the expert assessment (i.e., top-ranked IAS). In both lists, aquatic IAS belonging to the four thematic groups (plants, freshwater invertebrates, estuarine invertebrates, and vertebrates) were identified as having been introduced through various pathways from different regions of the world and classified according to their main functional feeding groups. Also, the latest update of the list of IAS of Union concern pursuant to Regulation (EU) No 1143/2014 includes only 12 top-ranked IAS identified for the Iberian Peninsula, while the national lists incorporate the vast majority of them. This fact underlines the great importance of taxa prioritisation exercises at biogeographical scales as a step prior to risk analyses and their inclusion in national lists. This HS provides a robust assessment and a cost-effective strategy for decision-makers and stakeholders to prioritise the use of limited resources for IAS prevention and management. Although applied at a transnational level in a European biodiversity hotspot, this approach is designed for potential application at any geographical or administrative scale, including the continental one.